Standardization of Berberis aristata DC and Nigella sativa L. Using HPTLC and GCMS and Their Antineoplasia Activity in 7,12-Dimethylbenz[a]anthracene-Induced Mouse Models - Mazhar, Mohd; Agrawal, S S (Frontiers in Pharmacology, 2021)
B. aristata and N.sativa are officially listed in, Indian Pharmacopeia, Ayurvedic & Siddha Pharmacopoeia of India. Due to its proven pharmacological activities, it became part of polyherbal formulations and prescribed for different ailments. With reverse pharmacology and their scientifical validation, as a result, more than 30 plus patents are filed on the different formulation of B.aristata and granted. N. sativa has been extensively studied for its therapeutic potential and shown to possess a wide spectrum of activities viz. as antihypertensive, antidiabetic, anticancer, and immunomodulatory. Thus the study is aimed to standardize the B.aristata and N.sativa and their anti neoplasia activity in 7,12-Dimethylbenz[a]anthracene induced mouse model. Molecular docking was done using the Schrodinger program Maestro 9.0. Herbal extracts and essential oil (B. aristata and N.sativa) were standardized and quantified using HPTLC (CAMAG) , GCMS (Agilent 2010 GC System ) with validated methods. 7,12-Dimethylbenz[a]anthracene administered orally once a week (1mg/200µl) to each animal except for normal control. Hematology, histopathology, and immunohistochemistry performed and data analyzed, depicted with graph pad and SPSS. In molecular docking, thymoquinone showed the highest docking score (9.519, 9.211 and 9.042 respectively) in the active sites of the active site pocket of IL6 (PDB ID: 4CNI and 5FCU), TNF (PDB ID: 2AZ5), and VEGF (PDB ID: 4KZN). Out of all four target site, thymoquinone and berberine showed good binding affinity with IL6 (PDB ID: 4CNI) than alpha and beta pinenes. HPTLC analysis of hydroalcoholic extract showed the presence of berberine in both qualitative and quantitative (5.4% berberine) and thymoquinone detected 0.17 % in the N.sativa extract. Gas chromatography-mass spectrometry for essential oil showed 26 compounds including ±Pinene. Leukocytes and erythrocyte of N sativa and B.aristata were analyzed and significant improvement was recorded (P < 0.05) and graphical presented. Mean survival time calculated by Kaplan meier method ( 119 days). Immunohistochemisty analysis was conducted namely TNF-𝛼 and VEGF and interpreted.